Asistensi Penerapan Nilai-Nilai Islami dalam Pembelajaran Akidah Akhlak di MTS Darunnajah - Tomi Bidjai; Kusno Setiadi; Resti Riancana; Vini Desiyanti Monoarfa; Nurhajja M Hadji; Adrianto Adrianto; Irma Irma (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
The application of Islamic values ​​in learning aqidah and akhlak at MTs Darunnajah aims to shape students' characters in accordance with Islamic teachings. This activity is carried out to improve the understanding and practice of Islamic values ​​in students' daily lives. The method used is a participatory approach, involving teachers and students in designing and implementing learning programs. The activity begins with a survey and observation to determine the conditions and needs of teaching in schools. Furthermore, training materials are prepared and delivered to students to introduce Islamic values ​​that can be applied in their lives. The results of this service show that most students begin to understand the importance of implementing Islamic values. Madrasahs need to continue this program in order to form better student characters and lead to the practice of Islamic teachings in everyday life.